2021
DOI: 10.1161/circresaha.121.318943
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling Complexity and Multipotentiality of Early Heart Fields

Abstract: Rationale: Extraembryonic tissues, including the yolk sac and placenta, and the heart within the embryo, work to provide crucial nutrients to the embryo. The association of congenital heart defects (CHDs) with extraembryonic tissue defects further supports the potential developmental relationship between the heart and extraembryonic tissues. Although the development of early cardiac lineages has been well-studied, the developmental relationship between cardiac lineages, including epicardium, and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 46 publications
5
93
0
Order By: Relevance
“…This model is supported by another recent finding that perturbations at the stage of cardiac mesoderm specification during directed differentiation led to no significant changes to the overall proportion of cardiomyocytes and non-myocytes (J. H. Lee et al 2017), suggesting that cells may determine whether they are cardiac or noncardiac cell types in the first few days of directed differentiation. Such a model would also be consistent with in vivo experiments that point to the existence of a cardiac multipotent cell prior to gastrulation (Meilhac et al 2004;Lescroart et al 2014;Devine et al 2014;Ivanovitch et al 2021;Zhang et al 2021). Simultaneously, strict spatiotemporal patterning of EPCAM at the onset of murine gastrulation and in embryonic stem cell differentiation has been shown to direct the appropriate segregation of EPCAM positive endoderm and EPCAM negative mesoderm and is necessary for cardiomyocyte production (Sarrach et al 2018).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This model is supported by another recent finding that perturbations at the stage of cardiac mesoderm specification during directed differentiation led to no significant changes to the overall proportion of cardiomyocytes and non-myocytes (J. H. Lee et al 2017), suggesting that cells may determine whether they are cardiac or noncardiac cell types in the first few days of directed differentiation. Such a model would also be consistent with in vivo experiments that point to the existence of a cardiac multipotent cell prior to gastrulation (Meilhac et al 2004;Lescroart et al 2014;Devine et al 2014;Ivanovitch et al 2021;Zhang et al 2021). Simultaneously, strict spatiotemporal patterning of EPCAM at the onset of murine gastrulation and in embryonic stem cell differentiation has been shown to direct the appropriate segregation of EPCAM positive endoderm and EPCAM negative mesoderm and is necessary for cardiomyocyte production (Sarrach et al 2018).…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, substantial cell death concomitant with cell growth is routinely observed during differentiation, and it is not known whether certain cells are predetermined to survive (Qiu et al 2017). In vivo evidence suggests that multipotent precursors that generate a variety of cardiac cells, including cardiomyocytes, vascular endothelial cells, and smooth muscle cells (but not cardiac fibroblasts), choose a fate at a point prior to gastrulation (Meilhac et al 2004;Devine et al 2014;Lescroart et al 2014;Ivanovitch et al 2021;Zhang et al 2021). That timing of cell type determination is earlier than would have been expected from previous markers proposed based on in vitro differentiation of cultured hiPS cells; hence, the timing of determination to these different cell types during directed differentiation remains unknown and may be earlier than has been previously suggested (L. Yang et al 2008;Kattman, Huber, and Keller 2006;Wu et al 2006;Moretti et al 2006;Bu et al 2009;Bondue et al 2008;Misfeldt et al 2009).…”
mentioning
confidence: 99%
“…The FHF cells express Hand1 and Hcn4 among other markers. Recently, an additional multipotent progenitor field anterior to the FHF, also expressing Hand1 , has been identified to contribute to myocardium of the left ventricle, atrioventricular canal, and the proepicardium ( Tyser et al., 2021 ; Zhang et al., 2021 ). While the FHF differentiates and forms the linear heart tube, the SHF is maintained in a proliferative progenitor state ( Prall et al., 2007 ).…”
Section: Overview Of Ra Signaling In Cardiogenesismentioning
confidence: 99%
“…The proepicardium is characterized by the ubiquitous expression of Tbx18 , Tcf21 , and Wt1 among other genes ( Lupu et al., 2020 ). The precise origins of the proepicardium are poorly understood, and recent insights reveal that it receives contributions from multiple progenitor populations ( Mommersteeg et al., 2010 ; Tyser et al., 2021 ; Zhang et al., 2021 ). It has been identified that a population anterior to the FHF has the potential to form myocardial components such as left ventricle, atrioventricular canal, and proepicardium ( Tyser et al., 2021 ; Zhang et al., 2021 ).…”
Section: Ra In Epicardial Developmentmentioning
confidence: 99%
“…And they also uncovered intraembryonic progenitor from the lateral plate mesoderm (LPM) and cardiac progenitor from the late extraembryonic mesoderm can contribute to the development of cardiomyocytes. 51 Collectively, these studies have utilized…”
Section: Trajectory Inference Discovers Transition States In Heart Developmentmentioning
confidence: 99%